Vancomycin-resistant Staphylococcus aureus (VRSA) from Nepal: a cocktail story - Dumre, SP (Nepalese Journal of Ophthalmology, 2012)
DOI: http://dx.doi.org/10.3126/nepjoph.v4i1.5879 NEPJOPH 2012; 4(1): 199-200